Advancing Green Banking Awareness in an Emerging Economy: Extending the GBCS with Green Satisfaction and Trust‑Driven Loyalty (Journal of Asian Development Studies, 2025)
This study revisits the role of Green Banking Awareness (GBA) in shaping downstream customer outcomes —Green Attitude (GA), Green Trust (GT), Green Loyalty (GL), and the newly introduced construct Green Satisfaction (GS) — in a large emerging economy context. We extend the Green Banking Consumer Scale (GBCS) by explicitly modelling GS and by situating the analysis in a market characterised by both high climate vulnerability and rapid financial inclusion. Using a structured questionnaire administered to educated banking customers (N = 384), we estimate a measurement and structural model. Reliability and validity are evaluated via Cronbach's α, Composite Reliability (CR), and Average Variance Extracted (AVE). The hypothesised structural paths are tested with Structural Equation Modelling (SEM). Fit indices meet accepted thresholds. GBA is strongly and positively associated with GT and GL, while its direct association with GA is weaker. GT is a robust antecedent of GL. GS emerges as a meaningful outcome of GBA and as a complementary lens for interpreting customer evaluations of banks' environmental performance. These results are directionally consistent with recent cross-country evidence and underscore that awareness and credible communication are prerequisites for trust-based loyalty. Banks should publicly verify green claims and integrate environmental performance into customer experience metrics. Regulators can advance green finance literacy and mandate standardised disclosure to close awareness gaps. Communication programs that translate technical ESG activities into relatable customer stories are likely to increase GS, GT, and GL. We re-specify the GBCS to include GS, synthesise the recent literature, and provide an empirically grounded, policy-relevant account of how awareness cascades into trust, satisfaction, and loyalty in sustainable banking.